Modified iron-based metal catalyst and preparation method thereof

By depositing inactive metal atoms of nanoscale thickness on the surface of the iron-based metal material, a dispersed distribution of nano-atom layers is constructed, which solves the problem of poor catalytic performance of traditional iron-based metal materials and achieves the goal of low-cost and high-catalytic active catalysts.

CN119819314AActive Publication Date: 2025-04-15HEFEI UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510051379.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-15
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Traditional iron-based metal materials have poor catalytic performance in the catalyst field, the alloying modification method is high and the limitations are large, and it is difficult for the internal atoms of the alloy to effectively participate in the reaction, resulting in waste of resources.

Method used

By depositing inactive metal atoms of nanoscale thickness on the surface of the iron-based metal material, a dispersed distribution of nanoatoms is constructed, and the catalytic reaction is directly involved in the catalytic reaction or activate the iron-based metal through the primary cell effect, and synergistically participate in the catalytic reaction.

Benefits of technology

The catalytic performance of modified iron-based metal catalysts has been significantly improved, costs have been reduced, resource utilization has been improved, and the goal of low-cost and high-catalytic active catalysts has been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819314A_ABST
    Figure CN119819314A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and particularly relates to a modified iron-based metal catalyst and a preparation method thereof.The catalyst is iron-based metal with non-active metal atoms deposited on the surface, the non-active metal atoms are deposited on the surface of the iron-based metal in a dispersed distribution mode, and the average deposition thickness of the non-active metal atoms is smaller than 50 nm. The invention creatively provides the catalyst for modifying the iron-based metal by using trace non-active metal elements, a nano-scale atomic layer structure can be constructed on the surface of the iron-based metal based on strong reactivity between the iron-based metal and non-active metal ions, the catalytic activity of the catalyst is remarkably improved, and the reaction is simple and easy to implement. The prepared modified iron-based metal catalyst has the dual advantages of low cost and high performance, and has a good application prospect in the field of catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular, relates to a modified iron-based metal catalyst and a preparation method thereof. Background Art

[0002] Iron-based metal materials are widely used in life and production due to their low cost, excellent magnetic and mechanical properties. In recent years, the performance and potential applications of iron-based metal materials, including iron-based amorphous alloys, in the field of chemical catalysis have received widespread attention. Improving the catalytic activity of iron-based metal materials is of great significance to expanding their application areas and meeting the strong market demand for low-cost catalysts.

[0003] At present, alloying is the main method for modifying iron-based metal materials. For example, adding a certain amount of Co or Ni elements to iron-based magnetic alloys can improve their soft magnetic properties; adding more than 10% Cr elements to steel can significantly improve its corrosion resistance. In the field of catalysts, researchers have found that adding 4wt% Co elements to iron-based amorphous alloys can improve their catalytic performance of Fenton-like reactions (New J.Chem., 2019, 43, 6126-6135), increasing their apparent rate constant by 38%. However, the Co element needs to be added during the smelting stage, and the complex process and high addition content significantly increase its cost. At present, the alloying process of iron-based metals is usually achieved during the material smelting stage by adding alloying elements with a mass fraction between 1% and 20%, so that they are evenly distributed in the alloy matrix, thereby regulating the physical and chemical properties of the alloy.

[0004] However, alloying as a modification method not only has high process and material costs, but also may significantly weaken the amorphous forming ability of the material, especially in amorphous alloys. This makes it difficult to achieve the expected alloy design performance requirements. In addition, since most chemical reactions occur at the interface, the atoms inside the alloy often cannot effectively participate in the reaction, resulting in low utilization of alloying elements and thus waste of resources.

[0005] Surface modification is an efficient and economical alternative strategy. At present, the surface modification of iron-based materials is mainly achieved by forming a coating with a thickness of 10 to 50 microns on its surface, such as copper plating, nickel plating, etc. However, since these surface coatings completely cover the surface of the substrate, such coatings are often used for corrosion protection of iron-based materials rather than for improving their reaction performance. Therefore, how to modify the surface of iron-based metal materials to improve their catalytic performance is of great significance to meet the market demand for low-cost, high-catalytic activity catalysts. Summary of the invention

[0006] In view of the problems of high cost, great limitations and unsatisfactory catalytic performance improvement of traditional iron-based metal materials using alloying modification methods, the present invention innovatively proposes a method for modifying the catalytic performance of iron-based alloys using trace inactive metal elements. Based on the strong reactivity of surface atoms of iron-based metals with inactive metal ions, a very small amount of inactive metal elements are deposited on the surface of the iron-based metal to construct a nanoscale atomic layer, which changes the atomic composition of the surface of the iron-based metal. These trace inactive metal atoms are dispersed on the surface of the iron-based metal, which can not only improve the catalytic activity of the iron-based metal, but also cooperate with the iron-based metal to participate in catalytic reactions, thereby significantly improving the catalytic effect on chemical reactions. The modified iron-based metal catalyst prepared by the present invention has the dual advantages of low cost and high performance, and has good application prospects in the field of catalysts.

[0007] Based on the above purpose, the technical solution adopted by the present invention is as follows:

[0008] In a first aspect, the present invention provides a modified iron-based metal catalyst, which is an iron-based metal with inactive metal atoms deposited on the surface; wherein the inactive metal atoms are deposited on the surface of the iron-based metal in a dispersed manner; and the average deposition thickness of the inactive metal atoms is <50nm.

[0009] In view of the problems of poor catalytic performance of traditional iron-based metal materials and high cost and great limitations of alloying modification methods, the present invention deposits inactive metal atoms with a thickness of nanometer level on the surface of iron-based metal materials. The catalytic performance of the resulting modified iron-based metal catalyst is significantly improved. This is because the deposited inactive elements can directly intervene in the catalytic reaction, activate the iron-based metal through the galvanic cell effect, and cooperate with the iron metal to participate in the catalytic reaction, thereby comprehensively improving the catalytic performance of the modified iron-based metal catalyst.

[0010] The modified iron-based metal catalyst is in powder or filament form. This type of modified iron-based metal catalyst has a relatively large specific surface area, which is more conducive to improving the catalytic effect on chemical reactions.

[0011] Preferably, the mass ratio of the inactive metal atoms to the iron-based metal is 0.001% to 0.8%:1.

[0012] Experiments have found that depositing a very small amount of inactive metal atoms on the surface of iron-based metals can significantly improve their catalytic activity.

[0013] Preferably, when the iron-based metal is an iron-based amorphous alloy, the mass ratio of the inactive metal atoms to the iron-based amorphous alloy is 0.05% to 0.5%:1, preferably 0.05% to 0.3%:1, and preferably 0.1% to 0.3%:1.

[0014] Experiments have shown that, within the range of trace deposition of inactive metal atoms, as the amount of inactive metal atoms deposited increases, the apparent rate constant of the modified iron-based metal catalyst in catalytic degradation of dyes first increases and then tends to stabilize. Inactive metal atoms have a relatively better catalytic effect within the above-mentioned deposition range.

[0015] Preferably, the iron-based amorphous alloy is at least one of a FeB-based amorphous alloy and a FeC-based amorphous alloy;

[0016] Among them, FeB series amorphous alloys include but are not limited to FeB amorphous alloys, FeSiB amorphous alloys, FePB amorphous alloys, FeBCSiCr amorphous alloys, and FeSiBNbCu amorphous alloys;

[0017] FeC-based amorphous alloys include, but are not limited to, FeCB amorphous alloys, FeCP amorphous alloys, FeCBP amorphous alloys, and FeCBSiP amorphous alloys.

[0018] Preferably, when the iron-based metal is a crystalline iron-based metal, the mass ratio of the inactive metal atoms to the crystalline iron-based metal is 0.02% to 0.2%:1.

[0019] Experiments have found that depositing inactive metal atoms on the surface of crystalline iron-based metals such as pure iron powder can also significantly improve their catalytic performance. The apparent rate constant of the modified iron-based metal catalyst in catalytic degradation of dyes first increases and then tends to stabilize. Inactive metal atoms have a relatively better catalytic effect within the above-mentioned deposition range.

[0020] Preferably, the crystalline iron-based metal is at least one of crystalline pure iron, iron-silicon alloy, iron-aluminum alloy, iron-carbon alloy, iron-boron alloy, iron-phosphorus alloy and other iron-based metals.

[0021] Preferably, the inactive metal atom is at least one of Cu, Ni, Ga, In, Sn, Ag, Ru, Rh, Pd, Pt, and Au.

[0022] In a second aspect, the present invention provides a method for preparing a modified iron-based metal catalyst, comprising the following steps:

[0023] The iron-based metal powder is mixed with an aqueous solution of inactive metal ions to react, so that the inactive metal atoms are deposited on the surface of the iron-based metal to obtain a modified iron-based metal catalyst;

[0024] The weight ratio of the inactive metal ions to the iron-based metal powder is 0.001% to 0.8%:1.

[0025] The present invention cleverly utilizes the strong reactivity between iron-based metals and inactive metal ions. By simply mixing the iron-based metal powder and the aqueous solution of the inactive metal ions, a nanometer-thick inactive metal atomic layer can be generated on the surface of the iron-based metal without adding additives. The inactive metal layer can activate the iron-based metal through the galvanic cell effect and can also cooperate with the iron metal to participate in the catalytic reaction, thereby greatly improving the catalytic activity of the iron-based metal material at an extremely low cost.

[0026] By analyzing the absorption spectra of inactive metal ions in the solution before and after the reaction, it was found that there were almost no free inactive metal ions in the solution after the reaction, indicating that the inactive metal ions can be completely deposited on the surface of the iron-based metal in this reaction. Therefore, by adjusting the relative content of inactive metal ions and iron-based metals in the reaction raw materials, the deposition amount of inactive metal ions on the surface of the iron-based metal can be controlled.

[0027] In addition, the present invention uses powdered iron-based metal as a reaction raw material, which has a relatively large specific surface area and increases the carrying capacity of inactive metal ions.

[0028] Preferably, the aqueous solution of inactive metal ions contains Cu 2+ 、Ni 2+ , Ga 3+ 、In 3+ Sn 2+ 、Ag + 、Ru 2+ 、Ru 3+ , Rh 3+ , Pd 2+ , Pt 2+ 、Au 3+ An aqueous solution of at least one metal ion.

[0029] Preferably, the aqueous solution of inactive metal ions includes an aqueous solution of copper sulfate, an aqueous solution of copper chloride, an aqueous solution of copper nitrate, an aqueous solution of nickel sulfate, an aqueous solution of nickel chloride, an aqueous solution of gallium chloride, an aqueous solution of indium chloride, a solution of stannous chloride, an aqueous solution of silver chloride, an aqueous solution of silver nitrate, an aqueous solution of silver sulfate, an aqueous solution of ruthenium sulfate, an aqueous solution of ruthenium chloride, an aqueous solution of ruthenium nitrate, an aqueous solution of rhodium sulfate, an aqueous solution of rhodium chloride, an aqueous solution of rhodium nitrate, an aqueous solution of palladium sulfate, an aqueous solution of palladium chloride, an aqueous solution of palladium nitrate, an aqueous solution of chloroplatinic acid, an aqueous solution of platinum nitrate, an aqueous solution of gold chloride, and an aqueous solution of potassium gold cyanide.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) Based on the strong reactivity between iron-based metals and inactive metal ions, the present invention constructs a nanometer-thick and diffusely distributed inactive metal atomic layer on the surface of the iron-based metal. The deposited inactive elements can directly intervene in the catalytic reaction, activate the iron-based metal through the galvanic cell effect, and cooperate with the iron metal to participate in the catalytic reaction, thereby comprehensively improving the catalytic performance of the modified iron-based metal catalyst.

[0032] (2) The present invention reacts powdered or filamentous iron-based metals with an aqueous solution of inactive metal ions to obtain a modified iron-based metal catalyst with a controllable amount of inactive metal atom deposition. The preparation process is extremely simple and the reaction is stable, which greatly reduces the cost of modifying iron-based metal materials.

[0033] (3) The iron-based metal of the present invention can be an iron-based amorphous alloy or a crystalline iron-based metal. After inactive metal atoms are deposited on its surface, its catalytic activity can be improved. Relatively speaking, the modified iron-based amorphous alloy catalyst has better catalytic performance than the modified crystalline iron-based metal.

[0034] In summary, the present invention is based on the strong reactivity between iron-based metals and inactive metal ions. Through a simple reaction between the iron-based metals and an aqueous solution of inactive metal ions, the controllable deposition of inactive metal atoms on the surface of the iron-based metal can be achieved. This modification process is extremely simple and easy, and the catalytic performance of the modified iron-based metal catalyst is greatly improved at a low cost. The amount of inactive metal is controlled at an extremely low level, which effectively ensures the low cost and high yield characteristics of the modification method, and shows good application prospects in the field of catalysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The performance comparison of FeSiBNbCu amorphous powder deposited with 0.03wt% copper atoms for catalytic Fenton-like reaction;

[0036] Figure 2 The performance comparison of FeSiBNbCu amorphous powder deposited with 0.06wt% copper atoms for catalytic Fenton-like reaction;

[0037] Figure 3 The performance comparison of FeSiBNbCu amorphous powder deposited with 0.25wt% copper atoms for catalytic Fenton-like reaction;

[0038] Figure 4 The effect of Cu atom deposition on the catalytic performance of FeSiBNbCu amorphous;

[0039] Figure 5 Comparison of XRD patterns of FeSiBNbCu amorphous powder deposited with 0.5wt% copper atoms and original amorphous powder;

[0040] Figure 6Cu2p XPS spectrum of FeSiB amorphous powder deposited with 0.03wt% copper atoms;

[0041] Figure 7 The catalytic performance of FeSiB amorphous alloy after depositing trace amounts of Cu atoms and Ag atoms is compared with that of the original amorphous alloy;

[0042] Figure 8 The effect of Cu atom deposition on the catalytic performance of modified pure iron;

[0043] Fig. 9 The absorption spectrum change of copper ions before and after the reaction of copper sulfate solution containing 0.3 mg copper ions with 1 g iron powder;

[0044] Fig.10 This is the XRD pattern of the modified powder in Example 16. DETAILED DESCRIPTION

[0045] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The test methods used in the examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial sources unless otherwise specified.

[0046] Example 1

[0047] This embodiment provides a modified iron-based metal catalyst, and the preparation method thereof is as follows:

[0048] 0.2g of FeSiBNbCu amorphous powder was mixed with 2mL of 80mg / L copper sulfate aqueous solution (containing 0.06mg of copper ions), and the mixture was shaken for 30s. After the two were fully reacted, the deposited product was collected, and the deposited product was washed with alcohol and dried to obtain an iron-based amorphous powder with 0.06mg of copper deposited on the surface, which was a modified iron-based metal catalyst. The mass ratio of Cu to iron-based amorphous (FeSiBNbCu) in the modified iron-based metal catalyst prepared in this embodiment was 0.03%:1.

[0049] The modified iron-based metal catalyst powder prepared in this example was subjected to a Fenton-like oxidation experiment, and 0.2 g of the original iron-based amorphous (FeSiBNbCu) powder was used as a control to carry out a Fenton-like oxidation experiment. The reaction medium was a solution containing 1 mmol / L hydrogen peroxide and 20 mg / L azo dye, the reaction medium solution was used in an amount of 200 mL, and the pH was 3.0. The experimental temperature was room temperature, and the experiment was carried out under mechanical stirring.

[0050] The normalized concentration-time curves of the modified iron-based metal catalyst powder prepared in this example and the original iron-based amorphous powder for catalytic degradation of azo dyes are shown in FIG. Figure 1 As shown in the figure, it can be seen that the catalytic performance of the iron-based amorphous material is significantly improved after a trace amount of Cu deposition. The improvement in performance is due to two factors: on the one hand, the deposited Cu atoms are distributed on the surface of the iron-based amorphous material and can activate the iron atoms; on the other hand, the surface Cu ions can synergistically catalyze the reaction.

[0051] Example 2

[0052] This embodiment provides a modified iron-based metal catalyst, and the preparation method thereof is as follows:

[0053] 0.2g of FeSiBNbCu amorphous powder was mixed with 2mL of 150mg / L copper sulfate aqueous solution (containing 0.12mg of copper ions), and the mixture was shaken for 30s. After the two were fully reacted, the deposited product was collected, and the deposited product was washed with alcohol and dried to obtain an iron-based amorphous powder with 0.12mg of copper deposited on the surface, which was a modified iron-based metal catalyst. The mass ratio of Cu to iron-based amorphous (FeSiBNbCu) in the modified iron-based metal catalyst prepared in this embodiment was 0.06%:1.

[0054] Take the same amount of the modified iron-based metal catalyst prepared in this example and the original iron-based amorphous powder (FeSiBNbCu) and refer to the Fenton-like oxidation experiment in Example 1 to obtain the normalized concentration-time curve of the two powders for catalytic degradation of azo dyes, as shown in FIG. Figure 2 It can be seen that the catalytic performance of the iron-based amorphous material is significantly improved after a trace amount of Cu deposition, and the effect of the modified iron-based metal catalyst at a reaction time of 2 minutes exceeds that of the original iron-based amorphous powder at a reaction time of 4 minutes.

[0055] Depend on Figure 1 , Figure 2 By comparison, it can be seen that the catalytic effect of the modified iron-based metal catalyst prepared in this example is better than that of the catalyst prepared in Example 1.

[0056] Example 3

[0057] This embodiment provides a modified iron-based metal catalyst, and the preparation method thereof is as follows:

[0058] 0.2g of FeSiBNbCu amorphous powder was mixed with 2mL of 640mg / L copper sulfate aqueous solution (containing 0.5mg copper ions), and the mixture was shaken for 30s. After the two were fully reacted, the deposited product was collected, and the deposited product was washed with alcohol and dried to obtain an iron-based amorphous powder with 0.5mg copper deposited on the surface, which was a modified iron-based metal catalyst. The mass ratio of Cu to iron-based amorphous (FeSiBNbCu) in the modified iron-based metal catalyst prepared in this embodiment was 0.25%:1.

[0059] Take the same amount of the modified iron-based metal catalyst prepared in this example and the original iron-based amorphous powder (FeSiBNbCu) and refer to the Fenton-like oxidation experiment in Example 1 to obtain the normalized concentration-time curve of the two powders for catalytic degradation of azo dyes, as shown in FIG. Figure 3 It can be seen that the catalytic performance of the iron-based amorphous material is further improved after a trace amount of Cu deposition.

[0060] Embodiments 4 to 6

[0061] Referring to the preparation method of the modified iron-based metal catalyst in Example 1, the only difference is that the mass of copper ions in the copper sulfate aqueous solution is different, as shown in Table 1, and the parts not described in the preparation method are the same as those in Example 1.

[0062] Table 1 Composition of modified iron-based amorphous powders of Example 4-Example 6

[0063] Example Iron-based amorphous quality Copper atomic mass Mass ratio of copper to iron-based amorphous Example 4 0.2g 0.03mg 0.015%:1 Example 5 0.2g 0.24mg 0.12%:1 Example 6 0.2g 1mg 0.5%:1

[0064] Referring to the Fenton-like catalytic reaction test method described in Example 1, an equal amount of original iron-based amorphous was used as a control to analyze the effect of the amount of Cu atom deposition on the catalytic performance of the catalyst powder. Figure 4 As shown in the figure, it can be seen that depositing a trace amount of Cu atoms can greatly improve the catalytic performance of iron-based amorphous. Within the test range, as the amount of Cu deposition increases, the catalytic performance of the alloy continues to rise.

[0065] The XRD patterns of FeSiBNbCu amorphous powder deposited with 0.5 wt% copper atoms (Example 6) and the original Fe-based amorphous alloy powder (FeSiBNbCu) are as follows: Figure 5 As shown in the figure, it can be seen that there is no obvious difference in the XRD spectra of the two alloys, and no characteristic peak of Cu is detected in the amorphous powder deposited with Cu. This is because the Cu content is low and a macroscopic Cu layer cannot be formed. This result indirectly shows that the formed Cu is a nanostructure.

[0066] Example 7

[0067] This embodiment provides a modified iron-based metal catalyst, and the preparation method thereof is as follows:

[0068] 1g of FeSiB amorphous powder was mixed with a copper sulfate aqueous solution containing 0.3mg of copper ions, and the two were fully reacted to collect the deposited product, and the deposited product was washed with alcohol and dried to obtain an iron-based amorphous powder with 0.3mg of copper deposited, which was a modified iron-based metal catalyst. The mass ratio of Cu to iron-based amorphous in the modified iron-based metal catalyst prepared in this embodiment was 0.03%:1.

[0069] The XPS spectrum of the modified iron-based metal catalyst powder prepared in this example is as follows: Figure 6 As shown, the test shows that the Cu element signal on the FeSiB amorphous surface is strong. After analyzing the spectrum, it is found that when the Cu atom deposition amount is only 0.03wt%, the content ratio of Cu element to Fe element in the nanometer depth of the FeSiB amorphous surface exceeds 25%, that is, 0.3mg of copper atoms are widely distributed on the surface of the iron-based amorphous powder. This also explains why the performance of the modified iron-based amorphous in the present invention is greatly improved.

[0070] According to the copper density and the amount of copper element deposited, it can be estimated that the average depth of the deposited Cu atomic layer is about 2.5nm. This shows that the strong reactivity of copper ions with iron-based amorphous materials causes Cu atoms to form a dispersed nanolayer on the surface of iron-based amorphous materials. This special structure can significantly improve the catalytic performance of the alloy. At the same time, it also proves the feasibility of using iron-based amorphous alloys as metal catalyst carriers.

[0071] Example 8

[0072] This embodiment provides a modified iron-based metal catalyst, and the preparation method thereof is as follows:

[0073] 1g of FeSiB amorphous powder was mixed with a copper sulfate aqueous solution containing 3mg of copper ions. After the two were fully reacted, the deposited product was collected, and the deposited product was washed with alcohol and dried to obtain an iron-based amorphous powder with 3mg of copper atoms deposited, which was a modified iron-based metal catalyst. The mass ratio of Cu to the iron-based amorphous alloy in the modified iron-based metal catalyst prepared in this embodiment was 0.3%:1.

[0074] Example 9

[0075] This embodiment provides a modified iron-based metal catalyst, and the preparation method thereof is as follows:

[0076] 1g of FeSiB amorphous powder was mixed with a silver nitrate aqueous solution containing 3mg of silver ions, and the two were fully reacted, and the deposited product was collected. The deposited product was washed with alcohol and dried to obtain an iron-based amorphous powder with 3mg of silver atoms deposited, which was a modified iron-based metal catalyst. The mass ratio of Ag to the iron-based amorphous alloy (FeSiB) in the modified iron-based metal catalyst prepared in this embodiment was 0.3%:1.

[0077] Take 1g of FeSiB amorphous powder, modified iron-based metal catalyst powder of Example 8 and Example 9 in equal amounts, and carry out Fenton-like catalytic test under neutral conditions according to the Fenton-like oxidation experimental method in Example 1. The apparent rate constants of different catalysts are as follows: Figure 7As shown, under neutral conditions, the catalytic performance of Examples 8 and 9 is significantly improved compared with the original iron-based amorphous alloy (FeSiB). It shows that the catalytic performance of the iron-based amorphous after the deposition of Cu and Ag is greatly improved. The reason for the stronger catalytic performance after the deposition of Cu atoms may be that Cu atoms can jointly catalyze Fenton-like reactions with Fe atoms, while Ag atoms can only enhance the reaction by enhancing the catalytic activity of Fe atoms.

[0078] Embodiments 10 to 16

[0079] Referring to the preparation method of the modified iron-based metal catalyst in Example 1, the difference is that in Examples 10 to 16, pure iron powder is used instead of iron-based amorphous alloy powder to react with copper sulfate solution. The specific method is as follows:

[0080] 1 g of pure iron powder was mixed with 2 mL of copper sulfate aqueous solution containing different amounts of copper ions for reaction, and the rest of the preparation method not described was the same as that of Example 1. The parameters involved in Examples 10 to 16 are shown in Table 2.

[0081] Table 2 Composition of modified iron powder catalyst in Examples 10 to 16

[0082] Example Pure iron powder quality Copper atomic mass Copper to iron powder mass ratio Example 10 1g 0.05mg 0.005%:1 Embodiment 11 1g 0.1mg 0.01%:1 Example 12 1g 0.3mg 0.03%:1 Example 13 1g 0.6mg 0.06%:1 Embodiment 14 1g 1.2mg 0.12%:1 Embodiment 15 1g 2.5mg 0.25%:1 Example 16 1g 5mg 0.5%:1

[0083] Referring to the Fenton-like oxidation test method in Example 1, an equal amount of pure iron powder was used as a control to analyze the effect of the Cu atom deposition amount on the apparent rate constant of the modified iron-based metal catalyst when catalyzing the Fenton-like reaction. Figure 8 As shown in the figure, it can be seen that the deposition of trace copper atoms greatly improves the catalytic performance of pure iron. Considering the cost and the effect of improving catalytic performance, the deposition amount of copper atoms of 0.02% to 0.2% is more appropriate.

[0084] The changes in the absorption spectrum of copper ions in the copper sulfate solution before and after the reaction of Example 12 were detected, and the results were as follows: Fig. 9 As shown, it can be seen that the trace amount of copper ions basically disappeared after the reaction, thus confirming that the copper element was completely deposited on the surface of the iron powder after the reaction.

[0085] XPS test of the modified powder in Example 16 shows that the content of Cu atoms is only 0.5%, and the proportion of metal atoms in the nanometer scale of the iron powder surface reaches 41%. This shows that Cu atoms are basically deposited on the iron powder surface in a dispersed distribution. From this, it can be estimated that the average depth of copper atoms is 25nm, which is much smaller than the thickness of the copper plating layer in the traditional sense (10-50μm).

[0086] The XRD pattern of the modified powder in Example 16 is as follows: Fig.10As shown, no obvious Cu crystalline diffraction peak was observed. This result further confirms the XPS test results, that is, due to the high dispersion and shallow depth of Cu atoms on the surface of the iron powder, they are highly diluted in the XRD test (detection depth ≥ 10 μm). This result also shows from the side that the formed Cu is a nanostructure.

Claims

1. A modified iron-based metal catalyst, characterized in that: The catalyst is an iron-based metal with inactive metal atoms deposited on the surface; the inactive metal atoms are deposited on the surface of the iron-based metal in a dispersed distribution manner; and the average deposition thickness of the inactive metal atoms is less than 50 nm.

2. The modified iron-based metal catalyst according to claim 1, characterized in that The mass ratio of the inactive metal atoms to the iron-based metal is 0.001% to 0.8%:

1.

3. The modified iron-based metal catalyst according to claim 1, characterized in that The iron-based metal is an iron-based amorphous alloy, and the mass ratio of the inactive metal atoms to the iron-based amorphous alloy is 0.05% to 0.5%:

1.

4. The modified iron-based metal catalyst according to claim 3, characterized in that The iron-based amorphous alloy is at least one of a FeB-based amorphous alloy and a FeC-based amorphous alloy; The FeB series amorphous alloys include FeB amorphous alloys, FeSiB amorphous alloys, FePB amorphous alloys, FeBCSiCr amorphous alloys and FeSiBNbCu amorphous alloys; The FeC-based amorphous alloys include FeCB amorphous alloys, FeCP amorphous alloys, FeCBP amorphous alloys and FeCBSiP amorphous alloys.

5. The modified iron-based metal catalyst according to claim 1, characterized in that The iron-based metal is a crystalline iron-based metal, and the mass ratio of the inactive metal atoms to the crystalline iron-based metal is 0.02% to 0.2%:

1.

6. The modified iron-based metal catalyst according to claim 5, characterized in that The crystalline iron-based metal is at least one of crystalline pure iron, iron-silicon alloy, iron-aluminum alloy, iron-carbon alloy, iron-boron alloy and iron-phosphorus alloy.

7. The modified iron-based metal catalyst according to claim 1, characterized in that The inactive metal atom is at least one of Cu, Ni, Ga, In, Sn, Ag, Ru, Rh, Pd, Pt, and Au.

8. The method for preparing the modified iron-based metal catalyst according to any one of claims 1 to 7, characterized in that: The steps include: The iron-based metal powder is mixed with an aqueous solution of inactive metal ions to react, so that the inactive metal atoms are deposited on the surface of the iron-based metal to obtain a modified iron-based metal catalyst; The weight ratio of the inactive metal ions to the iron-based metal powder is 0.001% to 0.8%:

1.

9. The preparation method according to claim 8, characterized in that: The aqueous solution of the inactive metal ions contains Cu 2 + 、Ni 2+ , Ga 3+ 、In 3+ Sn 2+ 、Ag + 、Ru 2+ 、Ru 3+ , Rh 3+ , Pd 2+ , Pt 2+ 、Au 3+ An aqueous solution of at least one metal ion.

Citation Information

Patent Citations

  • Transition metal-containing catalysts and catalyst combinations including transition metal-containing catalysts and processes for their preparation and use as oxidation catalysts

    CN101583425A

  • Preparation method of ozone catalyst by Cu / Fe bimetal material surface modification

    CN107199037A

  • Method for catalytically degrading methylene blue dye by amorphous alloy Fenton

    CN111747508A

  • Method for degrading azo dye by using chemical activator reinforced iron-based amorphous alloy

    CN117902712A

  • S-Fe0-coated Cu-Pd sponge iron-based trimetal catalyst as well as preparation method and application thereof

    CN118022768A